A Neuropsychological Rehabilitation Framework to Address Cognitive and Neurobehavioral Impairments After Strokes to the Anterior Communicating Artery - Cruces, Ramiro; Muñoz-García, Indhira; Palmer-Cancel, Santiago J.; Salas, Christian (Frontiers in Human Neuroscience, 2022)
Patients with strokes to the Anterior Communicating Artery (ACoA) pose an important challenge to rehabilitation teams due to a particular mix of cognitive and behavioral impairments (anosognosia, anterograde amnesia, prospective memory problems and executive dysfunction). These deficits often compromise engagement with rehabilitation, learning and generalization. The goal of this article is to describe the long-term presentation of a patient with an ACoA stroke (Mrs. B, a 60-year-old electric engineer) as well as her rehabilitation needs and the many challenges experienced by the rehabilitation team when attempting to facilitate functional, vocational and psychosocial recovery. Based on this case, and the existing literature, a neuropsychological rehabilitation framework to understand and address the specific problems and needs of this population is proposed. This framework demands rehabilitation teams to consider: the slow pattern of recovery of this population, the interaction between cognitive and behavioral impairments, the relevance of physical and social environments, the need to use personal projects and the need to include psychological and relational interventions.